2017
DOI: 10.1002/brb3.767
|View full text |Cite
|
Sign up to set email alerts
|

Social and environmental enrichment has different effects on ethanol and sucrose consumption in mice

Abstract: Background: Factors leading to the harmful consumption of substances, like alcohol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 101 publications
1
37
2
Order By: Relevance
“…Another limitation that the singlehoused animal model can face is handling by the researcher that produces experimental variations [12,20]. A recent study has shown that single-housed mice consume more alcohol in comparison with grouphoused animals [21]. However, in this study mice were given 20% ethanol without preliminary alcohol habituation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Another limitation that the singlehoused animal model can face is handling by the researcher that produces experimental variations [12,20]. A recent study has shown that single-housed mice consume more alcohol in comparison with grouphoused animals [21]. However, in this study mice were given 20% ethanol without preliminary alcohol habituation.…”
Section: Discussionmentioning
confidence: 93%
“…In these elegant studies, that include a social context and minimal human interference, similar alcohol consumption is reported [14,21,[28][29][30]. However, these studies have not focused on cue-induced craving after withdrawal.…”
Section: Accepted Manuscriptmentioning
confidence: 90%
“…This is contrary to later anxiolytic effects of enrichment on adolescent exposure to methamphetamine (Peterson and Hughes, 2017) and acute administration in adulthood of scopolamine (Hughes and Otto, 2013). It is also inconsistent with reductions in the reinforcing value and thus addiction potential of other drugs such as heroin (El Rawas et al, 2009), cocaine (Solinas et al, 2008) and ethanol (Holgate et al, 2017). However, there are also examples of enrichment having the opposite effect such as increasing ethanol's reinforcing value (Berardo et al, 2016) thereby detracting from any perceived beneficial quality of the manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, enrichment can influence drug effects in different ways. For example, it has been shown to either increase voluntary consumption and the reinforcing value of ethanol in rats (Berardo et al, 2016; Rockman et al, 1989) and mice (Rae et al, 2018), or have the opposite effect in both species respectively (Deehan et al, 2007; Holgate et al, 2017). It was therefore conceivable that BZP experienced repeatedly during adolescence in conjunction with enrichment might also differ in its subsequent effects on anxiety‐related behavior from those following acute administration of other drugs during adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…social isolation stress, chronic variable stress) can increase adult ethanol intake (e.g. [103][104][105][106][107], see also reviews: [108,109]). Elevated ethanol intake in other neurodevelopmental models may be linked to molecular changes such as decreased firing of dopaminergic VTA neurons in an LPS model [103], and may be related to altered anxiety-like states, as ethanol consumption in two-bottle free choice can be reduced by administration of anxiolytic adrenergic drugs [105].…”
Section: Ethanolmentioning
confidence: 99%